Mortality in schizophrenia: 30‐year nationwide follow‐up study. (13th June 2018) - Tanskanen, A.; Tiihonen, J.; Taipale, H.
Abstract : Objective: Recent reports suggest that the mortality gap between persons with schizophrenia and the general population is increasing. We investigated the mortality, age at death, and causes of death among persons diagnosed with schizophrenia and the general population in Finland during 1984–2014. Methods: All persons with schizophrenia in Finland were identified from hospital discharge register, and compared with the Finnish population aged 16 years and older during 1984–2014, based on data from Statistics Finland. Age at death and standardized mortality ratio (SMR) were calculated for each follow‐up year. Results: Mean age at death increased from 57.6 years in 1984 to 70.1 years in 2014 in persons with schizophrenia, and from 70.9 to 77.5 years in the general population. All‐cause SMR remained stable during the follow‐up (2.6 in 1984 and 2.7 in 2014). A major change was observed in SMR for suicides which decreased from 11.0 in 1984 to 6.6 in 2014 (−40%). The SMRs for cardiovascular and cancer deaths showed increasing trends. Conclusion: The longevity of persons with schizophrenia is improving at approximately the same rate as the general population but suicide rates have declined substantially. However, there is still a major disparity in mortality compared with general population.